Evaluation of successful introduction of plants from Lamiaceaefamily in the conditions of the Karaganda and Zhezkazgan cities - Butumbayeva, M.K.; Silant’eva, M.M. (Fundamental and Experimental Biology, 2020)
Evaluation of the success of plant introduction is an important stage of determining the possibility of industrial cultivation of individual taxa from an economic point of species. The success of the introduction is assessed on the basis of multi-year observations based on the evaluation of a number of indicators. The purpose of this study is to analyze the success of the introduction of species from the Lamiaceaefamily in the conditions of the cities of Karaganda and Zhezkazgan. The articlepresents the results of the assessment of the success of the introduction of plants of the Lamiaceaefamily on the territory of the cities of Karaganda (E.A. Buketov Karaganda University) and Zhezkazgan (Zhezkazgan Botanical Garden). In the city of Karaganda, 20 species from 13 genera were analyzed, in the city of Zhezkazgan — 14 species from 9 genera. Promising groups have been identified that allow recommending plants for industrial cultivation. In the conditions of the city of Karaganda, 6 species are classifiedas highly perspective, 4 species are perspective, 8 species are low perspective, and 2 species are not perspective. In the city of Zhezkazgan, 2 species are highly perspective, 3 species are perspective, 4 species are low perspective, and 5 species are not perspective. Plants suitable for cultivation in the conditions of the city of Karaganda and Zhezkazgan have been identified. The obtained results can be used for production of raw materials for food, aromatic and pharmaceutical industries.